Gut microbiota remodeling: A promising therapeutic strategy to confront hyperuricemia and gout - Wang, Zhilei; Li, Yuchen; Liao, Wenhao; Huang, Ju; Liu, Yanping; Li, Zhiyong; Tang, Jianyuan (Frontiers in Cellular and Infection Microbiology, 2022)
The incidence of hyperuricemia (HUA) and gout continuously increases and has become a major public health problem. The gut microbiota, which colonizes the human intestine, has a mutually beneficial and symbiotic relationship with the host and plays a vital role in the host's metabolism and immune regulation. Structural changes or imbalance in the gut microbiota could cause metabolic disorders and participate in the synthesis of purine metabolizing enzymes and the release of inflammatory cytokines, which is closely related to the occurrence and development of the metabolic immune disease HUA and gout. Considering the gut microbiota as an entry point to explore the pathogenesis of HUA and gout has become a new research hotspot. This review summarizes the characteristics of the gut microbiota in patients with HUA and gout. Meanwhile, the influence of different dietary structures on the gut microbiota, the effect of the gut microbiota on purine and uric acid metabolism, and the internal relationship between the gut microbiota and metabolic endotoxemia/inflammatory factors are explored. Moreover, the intervention effects of probiotics, prebiotics, and fecal microbial transplantation on HUA and gout are also systematically reviewed to provide a gut flora solution for the prevention and treatment of related diseases.